The choice among bank debt, non-bank private debt, and public debt: evidence from new corporate borrowings - Denis, David J; Mihov, Vassil T (Journal of Financial Economics, 2003)
Using a sample of 1,560 new debt financings, we examine the choice among bank debt, non-bank private debt, and public debt. The primary determinant of the debt source is the credit quality of the issuer. Firms with the highest credit quality borrow from public sources, firms with medium credit quality borrow from banks, and firms with the lowest credit quality borrow from non-bank private lenders. Non-bank private debt thus plays a unique role in accommodating the financing needs of firms with low credit quality. In addition, the choice of debt source is (weakly) influenced by managerial discretion.